The Temporal Order Effect in Children s Counterfactual Thinking - BYRNE, RUTH MARY JOSEPHINE (Mahwah, NJ: Lawrence Erlbaum Associates, 2005)
When adults think about how an outcome could have turned out differently, they tend to undo the events leading up to the outcome in regular ways. Consider a game in which two players could win a prize if they picked the same color card. The first picks black and the second picks red and so they lose. The temporal order effect refers to the tendency to think the players would have won if the second player had picked black. Adults also judge that the second player will feel more guilt and will be blamed more by the first player. We describe the results of an experiment on the temporal order effect in children?s counterfactual thoughts. The experiment shows that children aged six and eight years exhibited the standard temporal order effect when they thought about what might have been, but they differed in their judgments of guilt and blame. We discuss the implications of the findings for understanding the development of mental representations.
Proceedings of the 27th Annual Conference of the Cognitive Science Society
PUBLISHED
Keywords: Child psychology